Myxomycete with the ability to accumulate heavy metals. Diderma meyerae - Kryvomaz, Т. І.; Minter, D. W.; Michaud, A. (CABI, 2019)
Diagnostic features. Sporangia pale and usually sessile; distinguished from other nivicolous Diderma species by the non-reticulate capillitium, the double-layered peridium with an iridescent inner layer, and warted spores.
Keywords: myxomycetes; міксоміцети; Diderma meyerae